PERLINDUNGAN DAN PENEGAKAN HAM DI ASEAN TERHADAP MANUSIA PERAHU ROHINGYA DALAM STATUS SEBAGAI PENGUNGSI MENURUT HUKUM INTERNASIONAL - Jeremia Suluh Tampubolon; Abdul Rahman; Chairul Bariah (Journal of USU International Law, 2013)
ABSTRACTHuman rights are the rights of a person who has owned since the content itself, given by the Creator not the country or the board as well as host of others are going to be universally. Human rights is a part of the study of international law because of the nature and character of human rights itself is a defense mechanism and protection of the individual against the power of the State is vulnerable to abuse, as has been well prove in the history of mankind on Earth. Thesis research raises several issues, how the history of human rights in the international community, how the legal protection of ethnic and refugee status under international law, and how enforcement of human rights in ASEAN towards boat people Rohingya The research methods used in this thesis is done using the Normative Research Methods by collecting secondary data in Library Studies which this study originated from pure secondary data derived from books, articles, both from newspapers, websites, and magazines, and legislation. From the results of this study has concluded that human rights was born with the Magna Carta, the declaration of human rights by the United Nations and later adopted by several International Conventions. Problem of refugees in international law set out in the 1951 Convention on refugees accompanied by the 1967 Protocol on refugees. Upholding human rights on the Rohingya boat is not easy, see the difference of each legal instrument in the ASEAN countries recognize the existence of refugees in the country areas.Keywords : Human Rights, Etnic Rohingya, Refugees Status in ASEAN